-3(-4p+5)=5(6p+15)

Simple and best practice solution for -3(-4p+5)=5(6p+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-4p+5)=5(6p+15) equation:


Simplifying
-3(-4p + 5) = 5(6p + 15)

Reorder the terms:
-3(5 + -4p) = 5(6p + 15)
(5 * -3 + -4p * -3) = 5(6p + 15)
(-15 + 12p) = 5(6p + 15)

Reorder the terms:
-15 + 12p = 5(15 + 6p)
-15 + 12p = (15 * 5 + 6p * 5)
-15 + 12p = (75 + 30p)

Solving
-15 + 12p = 75 + 30p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-30p' to each side of the equation.
-15 + 12p + -30p = 75 + 30p + -30p

Combine like terms: 12p + -30p = -18p
-15 + -18p = 75 + 30p + -30p

Combine like terms: 30p + -30p = 0
-15 + -18p = 75 + 0
-15 + -18p = 75

Add '15' to each side of the equation.
-15 + 15 + -18p = 75 + 15

Combine like terms: -15 + 15 = 0
0 + -18p = 75 + 15
-18p = 75 + 15

Combine like terms: 75 + 15 = 90
-18p = 90

Divide each side by '-18'.
p = -5

Simplifying
p = -5

See similar equations:

| -14.3=5.7-4y | | 4a-b=.5 | | 3x+13-6x=15x+12x-5 | | x-(4.50+1.99+0.39)=13.12 | | 3x+2y-2=180 | | 3y=2x-15 | | y=x^2-8x+195 | | (2x^2+6x-3)+(2x^3-3x+2)= | | 3x+2=-3x+20 | | 2x+8=3x*x+4 | | -9-x=6x-79 | | -5x+11x-49=77 | | 2x+3+y+2=180 | | (r-3s+t)(2r-s+t)=0 | | 6y=4-1.69 | | 24=3(n+15) | | 3x+2=-3+20 | | 2(4y-5x)=6y-20 | | 9=4c-11 | | 18372747267284717839274728726472+98377778777777293771898472984727384774918999999999999999917373892946584456673485753756427426427538673=1 | | 2[4+2(5-x)-2x]=4(7+2x) | | -7x-2+x=-62 | | =(2x^3-7x^2+7x)+(2x^3+9x^2-14x) | | 5(2n+5)=6(8n+6)+5 | | 8x-3-3x=5x | | 35=8x-53 | | 2x+22=4x+4 | | (3x+5)+(2x-7)+x=180 | | 123456789+123456789=1 | | -7(n+4)+29=-4n-5 | | 49x^2+70x-11=0 | | (x+2)(12x^3-3x^2+x+1)=0 |

Equations solver categories